Additional information obtained with the Rasch model - Hurtado Mondoñedo, Luis (2014)
Learning evaluation includes the gathering of information, analysis of the information, interpretation of the obtained results and decision- making according to the analysis performed. The gathering of information then becomes the first stage of this process and the role of graded quizzes and exams are very important. These are the assessment tools with which we gather information that, after being analyzed, back up the reports about the student’s learning process. This analysis can be made in different degrees. Modern Theory provides the theoretical frame which allows a more refined interpretation of the observed grades. Here the Rasch’s Model is important. The purpose of the present article is to show additional information that can be gathered when analyzing student’s grades.